Orthognathic surgery and postoperative nausea and vomiting: An 11-year retrospective observational study - Takuma Watanabe; Ryuji Uozumi; Tatsuya Kawamura; Michinobu Sasaki; Risa Okada; Shu Inoue; Marina Kashiwagi; Shizuko Fukuhara; Shigeki Yamanaka; Sayaka Mishima; Akihiko Yamaguchi; Makoto Hirota (PLoS ONE, 2026)
Orthognathic surgery (OGS) is now widely performed, and postoperative nausea and vomiting (PONV) remains a common complication. Gastric decompression using a nasogastric tube (NT) is generally considered an effective prophylactic measure. In this retrospective observational study, we reviewed 667 OGS cases in 632 patients treated at our department between 2014 and 2024 to evaluate the role of NT placement in PONV by examining associations between clinical variables and PONV. Variables were extracted from electronic medical records, and descriptive statistics and annual trends were summarized. Univariable and multivariable logistic regression analyses were performed to examine associations with PONV. The mean age was 27.2 years, and 462 cases (69.3%) involved female patients. Single-jaw surgery was performed in 363 cases (54.4%) and double-jaw surgery in 304 cases (45.6%). Postoperative NT placement was used in 278 cases (41.7%), and PONV occurred in 53 cases (7.9%). The annual number of OGS cases increased from 48 in 2014 to 123 in 2024. Multivariable logistic regression analysis showed that age ≥ 30 years (odds ratio (OR), 0.43; 95% confidence interval (CI), 0.19–0.95; p = 0.04) and ondansetron administration (OR, 0.21; 95% CI, 0.04–0.97; p = 0.05) were associated with a lower risk of PONV, whereas postoperative NT placement was associated with a higher risk (OR, 4.03; 95% CI, 1.74–9.32; p = 0.001). These findings suggest that the number of OGS cases may be increasing, possibly reflecting growing societal awareness. In addition, postoperative NT placement may increase the risk of PONV, particularly in younger patients, while ondansetron may be effective in reducing PONV.